Establishment of a model house of community-energy for sustainable agriculture. A case study of Tan Phu Thanh Village, Hau Giang Province in the Vietnamese Mekong Delta. Issue 1 (1st March 2022) - Huu Chiem, Nguyen; Cong Thuan, Nguyen; Duy Can, Nguyen; Van Cong, Nguyen; Sy Nam, Tran; Duc Thanh, Tran; Thi Diem, Huynh; Shiratori, Yusuke; Fujimoto, Tokihiko
Abstract: This paper outlines the prerequisites and process of establishing of a community-based energy centre for sustainable agriculture practices in a rural village in the Vietnamese Mekong Delta. The centre was constructed by community consensus building and consisted of two main components including a community house and a community-biogas production system. The community house acts as a place where local people organize community activities such as traditional festivals and the production local products for local markets as well as community tourism. The community-biogas production system consists of a 41, 6 m 3 large biogas digester. The digester utilizes collected bio-degraded organic wastes from the local households and waste from animal husbandry as well as additional available green biomass such as water hyacinth. Methane produced will be used for cooking activities at the centre and delivered to the households in the community. Local people have contributed their own labours to build and manage the community-energy centre. Capacity building for the community is supported by experts of universities in both Vietnam and Japan. The community further intents to self-organize themselves to earn benefits through sustainable agricultural production such as planting organic vegetable and fruit trees, animal and fish raising, etc. This model is the first step in promoting the village as the "the most beautiful village" to clean up and promote environmental and sustainable technologies in the village. Furthermore, it is also a good option for inclusion in upgrading criteria for new rural development issued by Vietnamese government.